2014
DOI: 10.1126/science.1254214
|View full text |Cite
|
Sign up to set email alerts
|

A local clue to the reionization of the universe

Abstract: Identifying the population of galaxies that was responsible for the reionization of the universe is a long-standing quest in astronomy. We present a possible local analog that has an escape fraction of ionizing flux of 21%. Our detection confirms the existence of gaps in the neutral gas enveloping the starburst region. The candidate contains a massive yet highly compact star-forming region. The gaps are most likely created by the unusually strong winds and intense ionizing radiation produced by this extreme ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
263
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(275 citation statements)
references
References 23 publications
11
263
1
Order By: Relevance
“…In the high-mass range we find that the escape fraction is very high in a few haloes in which feedback was so violent that it removed most of the dense gas in the centre of the halo, causing large outflows. Recent observations have indeed found evidence for leaking ionizing radiation in one such object (Heckman et al 2011;Borthakur et al 2014). Observationally constraining the escape fraction during the epoch of reionization may be possible by targetting strongly lensed galaxies and look for features in the spectra that indicate a high escape fraction ).…”
Section: Discussionmentioning
confidence: 99%
“…In the high-mass range we find that the escape fraction is very high in a few haloes in which feedback was so violent that it removed most of the dense gas in the centre of the halo, causing large outflows. Recent observations have indeed found evidence for leaking ionizing radiation in one such object (Heckman et al 2011;Borthakur et al 2014). Observationally constraining the escape fraction during the epoch of reionization may be possible by targetting strongly lensed galaxies and look for features in the spectra that indicate a high escape fraction ).…”
Section: Discussionmentioning
confidence: 99%
“…Only three objects are known as LyC leakers, and their absolute escape fraction 1 is only a few percent (Bergvall et al 2006;Leitet et al 2013;Borthakur et al 2014). The vast majority of known high-redshift galaxies are also opaque to their own ionising radiation, as demonstrated by the success of the well-known Lyman-break selection (as emphasised recently in Cooke et al 2014).…”
Section: Ionising Continuum Leakage From Galaxiesmentioning
confidence: 99%
“…The object 0921+45 of the leaking canditates listed by Heckman et al does not meet our criteria for LyC leakage because of its large Lyα absorption trough around the systemic redshift, indicating large amounts of neutral gas and dust. It has recently been observed in the LyC continuum, and its absolute escape fraction is indeed low (∼1%), although the relative escape is higher (∼21% Borthakur et al 2014). Of the non-leakers, three out of four have v peak 150 km s −1 and no Lyα escape bluewards of the systemic redshift.…”
Section: Lyman-break Analoguesmentioning
confidence: 99%
“…The success of the selection method of I16a,b in finding LyC leakers at high O 32 ratios may thus be related to compactness, which together with very strong emission lines indicating a high specific SFR implies a high surface density of star formation. Heckman et al (2001Heckman et al ( , 2011 and Borthakur et al (2014) have suggested that strong star formation like this results in strong outflows that clear channels in the ISM, allowing thus the escape of Lyman continuum photons.…”
Section: In Terms Of Their Very High Equivalent Widths Of [O Iii]mentioning
confidence: 99%